Obtuário Frederic Mather Lord (1912-2000) - Wainer, Howard; Stocking, Marthe (Estudos em Avaliação Educacional, 2000)
<span style="font: 13px/normal verdana, arial; color: #000000; text-transform: none; text-indent: 0px; letter-spacing: normal; word-spacing: 0px; float: none; display: inline !important; white-space: normal; background-color: #ffffff;">Pequeno texto em inglês sobre Frederic Mather Lord